A Trivial Approach for Achieving Smart City: A Way Forward towards a Sustainable Society - Jnr, Bokolo Anthony; Mazlina, Abdul Majid; Awanis, Romli (IEEE, 2018)
Research and development related to smart city is evolving as a response to the issues faced by cities mostly in developing countries. However, prior studies are mostly focused on technical perspective which alone cannot lead to a sustainable society. Accordingly, this study develops a trivial approach that identifies crucial dimensions to be considered in achieving and improving city potential in being a smart city. Moreover, a qualitative research method was adopted by carrying out a single case study to confirm the identified dimensions. The data was collected through archival research technique and semi-structured interviews from practitioners based in Malaysia. Findings from this study indicate that cities should incorporates governance, mobility, living, facilities, services, environmental, social, economic, technologies and information to achieve a sustainable, prosperous and inclusive future for its citizens. Significantly, the developed trivial approach can be adopted by sustainable city managers in planning, designing, deploying and monitoring of sustainable city goals towards a sustainable society for future generations to come.